2014
DOI: 10.1002/casp.2216
|View full text |Cite
|
Sign up to set email alerts
|

Student Voice for School‐Climate Improvement: A Case Study of an Urban Middle School

Abstract: This case study used a student voice program in an urban middle school in the southeastern United States to examine the validity of three theoretically derived pathways through which student voice may affect positive school climate. First, using a youth participatory action research process to identify barriers to learning, analyse their root causes, and advocate for solutions to school administration allowed students to influence minor school policies and implement anti‐bullying, classroom‐behaviour‐monitorin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
57
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 50 publications
(60 citation statements)
references
References 32 publications
0
57
0
Order By: Relevance
“…Five articles reported that adults had an increased understanding of the experiences and needs of diverse youth because of the project (Brown, ; Galletta & Jones, ; McIntyre, Chatzopoulos, Politi, & Roz, ; Ozer & Wright, ; Sanchez, ). Specifically, adults were more willing to engage in diversity‐related discussions with young people at school (Ozer & Wright, ); relationships between students and teachers were improved (Mitra, ; Voight, ); and adults described engaging in more reflexivity regarding power dynamics between youth and adults (Bertrand, ; McIntyre et al., ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Five articles reported that adults had an increased understanding of the experiences and needs of diverse youth because of the project (Brown, ; Galletta & Jones, ; McIntyre, Chatzopoulos, Politi, & Roz, ; Ozer & Wright, ; Sanchez, ). Specifically, adults were more willing to engage in diversity‐related discussions with young people at school (Ozer & Wright, ); relationships between students and teachers were improved (Mitra, ; Voight, ); and adults described engaging in more reflexivity regarding power dynamics between youth and adults (Bertrand, ; McIntyre et al., ).…”
Section: Resultsmentioning
confidence: 99%
“…Youths’ participation in inquiry also led to changes among their peer groups. Four of these studies reported that the project resulted in changes to peer groups’ knowledge or behavior regarding either physical activity or nutrition (Dzewaltowski et al., ; Frerichs, Sjolie, Curtis, Peterson, & Huang, ; Yoshida, Craypo, & Samuels, ) or bullying (Voight, ). Similarly, Langhout, Collins, and Ellison () reported that the youth had strengthened peer networks, linkages between home and school, and connections to intermediary community‐based organizations.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Checkoway and Richards‐Schuster () described how disadvantaged youth in one school used a youth‐organizing strategy to change harsh disciplinary policies, protest placement of hazardous waste by their schools, and educate their community about overcriminalization of local youth. Other qualitative studies of youth civic participation have shown how young people, working in concert, have effected change in school facilities and college preparatory classes (Shah & Mediratta, ), violence‐prevention programming (Voight, in press; Warren, Mira, & Nikundiwe, ), the tracking of English‐language learners (Speer, ), and school‐based racial (Christens & Kirshner, ) and socioeconomic (Morrell, ) inequalities.…”
Section: Setting Characteristics and Civic Participationmentioning
confidence: 99%